2004
DOI: 10.1086/420699
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Structure in the Circumstellar Disk around AB Aurigae

Abstract: We present a near-infrared image of the Herbig Ae star AB Aur obtained with the Coronagraphic Imager with Adaptive Optics mounted on the Subaru Telescope. The image shows a circumstellar emission extending out to a radius of AU, with a double spiral structure detected at AU. The surface brightness r p 580 r p 200-450 decreases as , steeper than the radial profile of the optical emission possibly affected by the scattered Ϫ3.0‫1.0ע‬ r light from the envelope surrounding AB Aur. This result, together with the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
209
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(234 citation statements)
references
References 28 publications
22
209
1
Order By: Relevance
“…Nearinfrared scattered-light imaging observations probe the spatial distribution of small grains, approximately micron-sized or smaller, that are well coupled to the gas (Pinilla et al 2012;Zhu et al 2012). These studies have revealed spiral arms in a growing number of disks (Figure 1), both prominent near-symmetric twoarm spirals (e.g., Grady et al 2013;Benisty et al 2015) and more flocculent multiarm spirals on smaller scales and at lower contrast (e.g., Fukagawa et al 2004;Hashimoto et al 2011). Spiral arms can be produced by either gravitational instability (e.g., Rice et al 2003;Lodato & Rice 2004;Stamatellos & Whitworth 2008;Kratter et al 2010;Kratter & Lodato 2016) or the presence of massive companions (gas giant to stellar masses; e.g., Kley & Nelson 2012;Zhu et al 2015;Muñoz & Lai 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nearinfrared scattered-light imaging observations probe the spatial distribution of small grains, approximately micron-sized or smaller, that are well coupled to the gas (Pinilla et al 2012;Zhu et al 2012). These studies have revealed spiral arms in a growing number of disks (Figure 1), both prominent near-symmetric twoarm spirals (e.g., Grady et al 2013;Benisty et al 2015) and more flocculent multiarm spirals on smaller scales and at lower contrast (e.g., Fukagawa et al 2004;Hashimoto et al 2011). Spiral arms can be produced by either gravitational instability (e.g., Rice et al 2003;Lodato & Rice 2004;Stamatellos & Whitworth 2008;Kratter et al 2010;Kratter & Lodato 2016) or the presence of massive companions (gas giant to stellar masses; e.g., Kley & Nelson 2012;Zhu et al 2015;Muñoz & Lai 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, spatially resolved dust and molecular line observations in the millimeter and sub-millimeter domain (e.g., Mannings & Sargent 1997;Semenov et al 2005), together with scattered light coronographic imaging (e.g., Fukagawa et al 2004, Grady et al 2005 provided direct evidence that Herbig Ae/Be stars are effectively surrounded by a disk (for a detailed review about Herbig Ae/Be stars see Waters & Waelkens 1998). 1 The origin of the H i emission lines in Herbig Ae/Be stars is in fact controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, however, the observed visibility variation could not be modeled with the wind alone so we considered an additional component producing an extended continuum emission. This component could come from the extended reflection nebulosity around the system, already reported by several authors (Grady et al 1999b;Fukagawa et al 2004;Millan-Gabet et al 2006). In practice, we used this secondary source to reproduce the modulation of the visibility in the continuum.…”
Section: Modeling and Discussionmentioning
confidence: 99%
“…AB Aur is surrounded by a complex combination of gasrich and dust-dominated structures probed on large scales by imaging. Using the HST, Grady et al (1999b) detected extended nebulosity and circumstellar material at all position angles out to 1320 AU in the R-band, whereas Fukagawa et al (2004) detected a double spiral structure at 200−450 AU in the Hband. Spatially resolved observations at high angular resolution at near-infrared, thermal infrared, and millimetric wavelengths have shown the presence of a circumstellar disk (Millan-Gabet et al 2001;Eisner et al 2004), rotating at non-Keplerian velocities (Piétu et al 2005).…”
Section: The Target: Ab Aurigaementioning
confidence: 99%